The Effect Of Environmental, Social, And Governance Score On Stock Returns: The Moderating Role Of Company Size On The Indonesiann Stock Exchange - Muh. Faiz Rhamdani; Naning Margasari (Eduvest - Journal of Universal Studies, 2025)
This study aims to analyze the effect of the Environmental, Social, and Governance (ESG) dimensions on stock returns and test the moderating role of company size in companies listed on the LQ45 Index of the Indonesian Stock Exchange. This study uses a quantitative approach with purposive sampling and obtains 17 companies as samples for the 2019–2024 period. The data are analyzed using panel data regression and moderation regression to test the relationships between variables. The results show that the environmental score has a negative and significant effect on stock returns, the social score has a positive and significant effect on stock returns, while the governance score has no significant effect on stock returns. In addition, company size does not strengthen the relationships between the three ESG dimensions and stock returns. These findings provide practical implications for investors in portfolio selection by emphasizing social performance over environmental costs, for managers in optimizing ESG resource allocation toward high-impact social initiatives, and for policymakers in developing regulations that better align environmental investments with market incentives to enhance the effectiveness of sustainability practices in driving stock performance.